LEGAL ANALYSIS OF PATENT RIGHT PROTECTION IN THE DIGITAL ERA: A CASE STUDY OF THE USE OF BLOCKCHAIN TECHNOLOGY - Arief, Anggreany; Dwi Putri, Andi Istiana Inayah; Umar Gazali, Indrahayu; Asmah, Asmah (Yayasan Education and Social Center, 2025)
The digital era is driving significant transformations in the protection of intellectual property rights, including patent rights. The emergence of blockchain technology, with its characteristics of decentralization, immutability, and transparency, offers new opportunities to strengthen patent protection, but also raises legal challenges related to validity, jurisdiction, and data privacy. This study is to evaluate the legal ramifications of patent infringement in the digital age and investigate the prospective implementation of blockchain technology within Indonesia's patent protection framework. The method used is normative juridical with a statutory approach and qualitative analysis of primary and secondary legal materials. The results show that blockchain has great potential in creating a more efficient and transparent patent protection mechanism, but its implementation requires legal reform and recognition of digital evidence. This study underscores the importance of a flexible and comprehensive legal framework to ensure that patent protection in Indonesia remains responsive to advancements in digital technology.